Convergent validity of four instruments for measuring posttraumatic stress disorder. - Ljubotina, Damir; Muslić, Ljiljana (2003)
Three instruments for measuring posttraumatic stress reactions, Mississippi Combat Related Scale (M-PTSD, 35 items), Impact of Event Scale – Revised (IES-R, 22 items), and Watson PTSD Interview (PTSD-I, 17 items), were administered to a sample of 154 war veterans. High correlations were found between total scale results measured by these instruments. The correlations ranged from 0.866 to 0.900, the same range was found among the first principal components defined by these three instruments (correlations ranging from 0.883 to 0.906). As a fourth measure, shorter version of the Mississippi scale (Short M-PTSD) consisting of 11 items taken from the original one was used. The correlation of this short questionnaire with the total scale results of the Mississippi scale was 0.970, while its correlation with the other parts of the M-PTSD scale was 0.932. Reliability of internal consistency for all four measures was rather high and varies from a=0.914 (for IES-R) to a=0.966 (for M-PTSD). Results obtained on this sample showed a high convergent validity of all four PTSD measures we used.
Projekt MZOS
ENG